Harmony of Local Wisdom: Building the Image of Madrasah to Increase Competitiveness - Norman, Efrita; Firmansyah, Abd Muiz; Wahib, Abd (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
This research aims to analyze the branding image of madrasah based on local wisdom to provide a unique and attractive identity for the community in order to increase the competitiveness of madrasah. The research method used is a qualitative case study type approach. Data collection techniques are carried out through observation, interviews and documentation. Data analysis was carried out using the Miles and Huberman data analysis model, which includes stages of data reduction, data display, and conclusion. The research results show that implementing Local Wisdom-Based Branding Image is carried out through several stages, including Identification of Advantages, Needs Analysis, Local Wisdom Program, and Program Evaluation. The implication of Branding images based on Local Wisdom is that madrasah can have a unique identity easily recognized by the public, become a favourite according to environmental characteristics, and improve branding according to their local wisdom.